Detection of anti-desmoglein antibodies in oral lichen planus: What do we know so far - Didona, Dario; Hertl, Michael (Frontiers in Immunology, 2022)
Oral lichen planus (OLP) is an inflammatory disease of the oral mucosa. Clinically, two main subsets are described, namely non-erosive and erosive OLP. While non-erosive OLP is usually responsive to local therapies, erosive OLP is often refractory also to systemic therapies and extremely reduces the quality of life of the patients. Furthermore, in some erosive OLP cases different autoantibodies have been detected, including anti-desmoglein 1 and 3 autoantibodies, and anti-bullous pemphigoid 180 and 230 autoantibodies. However, their potential role is still not clear. In this paper, we reviewed the literature about the detection of autoantibodies against desmoglein 1 and 3, the main target antigens of pemphigus vulgaris, in patient with OLP, summarizing the more recent insights on this topic.